Benznidazole, the trypanocidal drug used for Chagas disease, induces hepatic NRF2 activation and attenuates the inflammatory response in a murine model of sepsis - Lambertucci, Flavia (2017)
Molecular mechanisms on sepsis progression are linked to the imbalance between reactive oxygen species (ROS) production and cellular antioxidant capacity. Previous studies demonstrated that benznidazole (BZL), known for its antiparasitic action on Trypanosoma cruzi, has immunomodulatory effects, increasing survival in C57BL/6 mice in a model of polymicrobial sepsis induced by cecal ligation and puncture (CLP). The mechanism by which BZL inhibits inflammatory response in sepsis is poorly understood. Also, our group recently reported that BZL is able to activate the nuclear factor erytroide-derived 2-Like 2 (NRF2) in vitro. The aim of the present work was to delineate the beneficial role of BZL during sepsis, analyzing its effects on the cellular redox status and the possible link to the innate immunity receptor TLR4. Specifically, we analyzed the effect of BZL on Nrf2 regulation and TLR4 expression in liver of mice 24 hours post-CLP. BZL was able to induce NRF2 nuclear protein localization in CLP mice. Also, we found that protein kinase C (PKC) is involved in the NRF2 nuclear accumulation and induction of its target genes. In addition, BZL prompted a reduction in hepatic CLP-induced TLR4 protein membrane localization, evidencing its immunomodulatory effects. Together, our results demonstrate that BZL induces hepatic NRF2 activation with the concomitant increase in the antioxidant defenses, and the attenuation of inflammatory response, in part, by inhibiting TLR4 expression in a murine model of sepsis.